Unintentional injury deaths among American Indian residents of the Fort Apache Indian Reservation, 2006–2012. Issue 6 (30th March 2019) - Kenney, Anne; Shields, Wendy; Hinton, Alexandra; Larzelere, Francene; Goklish, Novalene; Gardner, Kyle; Frattaroli, Shannon; Barlow, Allison
Abstract : This study aims to describe the epidemiology of unintentional injury deaths among American Indian residents of the Fort Apache Indian Reservation between 2006 and 2012. Unintentional injury death data were obtained from the Arizona Department of Health Services and death rates were calculated per 100 000 people per year and age adjusted using data obtained from Indian Health Service and the age distribution of the 2010 US Census. Rate ratios were calculated using the comparison data obtained through CDC's Web-based Injury Statistics Query and Reporting System. The overall unintentional injury mortality rate among American Indians residing on the Fort Apache Indian Reservation between 2006 and 2012 was 107.0 per 100 000. When stratified by age, White Mountain Apache Tribe (WMAT) mortality rates for all unintentional injuries exceed the US all races rate except for ages 10–14 for which there were no deaths due to unintentional injury during this period. The leading causes of unintentional injury deaths were MVCs and poisonings. Unintentional injuries are a significant public health problem in the American Indian and Alaska Native communities. Tribal-specific analyses are critical to inform targeted prevention and priority setting.